2018
DOI: 10.1051/shsconf/20184610005
|View full text |Cite
|
Sign up to set email alerts
|

Effets de l'âge d’immersion sur la compréhension initiale d’expressions modales épistémiques en français L2

Abstract: Alors qu'il est établi qu'à l'âge adulte le locuteur précoce d'une langue seconde dépasse dans de nombreux tests de performance le locuteur tardif, une question majeure reste de savoir si dès le stade initial l'enfant dispose d'une forte capacité acquisitive ou d'une marge de progression plus large. Notre étude observe si dans les 15 premiers mois d'exposition au français, des locuteurs enfants, adolescents et adultes de l'arabe syrien (L1) comprennent la valeur d'épistémicité de différentes expressions modale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Use of basic formulaic expressions such as non (lo)so ("I don't know") was also observed as a substitute for a modal, indicating "zero probability" (p. 312). In a more recent study, Granget et al (2018) confirmed the comprehension advantage for adult learners of L2 French epistemic modality in comparison with child and adolescent L2 learners.…”
Section: Universal Path Of Modal Acquisitionmentioning
confidence: 60%
See 1 more Smart Citation
“…Use of basic formulaic expressions such as non (lo)so ("I don't know") was also observed as a substitute for a modal, indicating "zero probability" (p. 312). In a more recent study, Granget et al (2018) confirmed the comprehension advantage for adult learners of L2 French epistemic modality in comparison with child and adolescent L2 learners.…”
Section: Universal Path Of Modal Acquisitionmentioning
confidence: 60%
“…A possible factor here is the late acquisition of epistemic meaning individually in both L1 and in L2 (Giacalone Ramat, 1992;Granget et al, 2018;Ozturk & Papafragou, 2015;Traugott & Dasher, 2004) and diachronically from pragmatic and lexical means to grammaticalized forms (Bybee et al, 1994). If Giacalone-Ramat's hypothesis regarding L2 modal acquisition is correct, longitudinal studies following L2 learners from their beginner to more advanced stages would be able to show in what ways L2 acquisition takes place.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…Use of basic formulaic expressions such as non (lo)so ('I don't know') was also observed, as a substitute for a modal, indicating "zero probability" (p. 312). In a more recent study, Granget et al (2018) In short, studies on grammaticalisation and individual development suggest that modality in both L1 and L2 language acquisition, as well as in diachronic processes, develops from pragmatic and lexical means to grammaticalised verb forms. This is explained by the fact that at early stages of acquisition language users do not have the grammatical (morphological) means to mark temporal and modal relations.…”
Section: Universal Path Of Modal Acquisitionmentioning
confidence: 99%
“…A possible factor is related to the late acquisition of epistemic meaning individually in both L1 and in L2 (Giacalone Ramat, 1992;Granget et al, 2018;Ozturk & Papafragou, 2015;Traugott & Dasher, 2004) and diachronically from pragmatic and lexical means to grammaticalised forms (Bybee et al, 1994). If Giacalone-Ramat's hypothesis regarding L2 modal acquisition is correct, longitudinal studies following L2 learners from their beginner to more advanced stages would be able to show in what ways L2 acquisition takes place.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%